The Effect of Breast Care and Oxytocin Massage on Breast Milk Production in Postpartum Mothers in the Working Area of Pataruman Public Health Center III Banjar City - Mentari Ramadhini; Citra Hadi Kurniati (UM Purwokerto Press, 2021)
The postpartum period refers to the first 42 days after childbirth. Breast milk contains the most appropriate and complete nutrient. Besides, it always adapts to the needs of the baby. There are several benefits of breast milk for babies the number of calories in breast milk can meet the needs of the baby, breast milk contains protective substances, and it strengthens the bond between a mother and her baby. Breast care stimulates prolactin, the hormone which helps milk production to facilitate breast milk. Oxytocin massage stimulates the posterior pituitary to release oxytocin, thus breast milk production is increased. This research aimed to determine the effect of breast care and oxytocin massage on breast milk production of postpartum mothers. In this research, the pre-experimental method was employed with a two-group pretest-posttest design. Most of the research respondents were 20-35 years old, multiparas, and graduated from junior and senior high school. Before breast care and oxytocin massage were conducted to 27 (93%) and 24 (86%) postpartum mothers respectively, most of them had low breastmilk supply. While, after the treatments were given to 27 (93%) postpartum mothers with breast care, and 24 (86%) postpartum mothers with oxytocin massage, most of the respondents had better milk production. The Mann Whitney test held after breast care and oxytocin massage indicated that p-value was 0.000 (p<0,05) for both variables. There is an effect of breast care and oxytocin massage on breast milk production of postpartum mothers.